Pengaruh Perencanaan, Transparansi dan Akuntabilitas Pengelolaan Dana Desa Terhadap Potensi Pencapaian Tujuan SDGs Desa (Studi Kasus di Desa Naiola Timur) - Maria Yunita Kosat; Fransiskus Marlon Reu; Agnes Kidi Beda Mudamakin (Politeknik Ganesha Medan, 2025)
This study aims to analyze the influence of planning, transparency, and accountability in village fund management on the achievement of Village SDGs in Naiola Timur Village. The background of this study is based on the condition that, despite Naiola Timur Village receiving village funds every year, its status is still classified as an underdeveloped village, and the implementation of SDG support programs is not yet optimal. The research population comprises the entire community of Naiola Timur Village, with a sample of 60 respondents selected through purposive sampling, consisting of village officials, BPD representatives, community leaders, and beneficiaries. The research used a quantitative approach with multiple linear regression assisted by SPSS. After adjusting the data by removing outliers to meet the assumption of normality, the results showed that planning and accountability had a significant positive effect on the achievement of village SDGs, while transparency had no significant effect. Simultaneously, all three variables were found to have a significant effect on the achievement of village SDGs. These findings emphasize the importance of participatory, accountable, and targeted village fund management as a prerequisite for achieving sustainable village development, and provide empirical evidence on how village fund management practices can influence the implementation of SDGs at the local level.